TINJAUAN HUKUM ISLAM TERHADAP DEPOSITO PERBANKAN (An-Nisbah: Jurnal Ekonomi Syariah, 2015)
One fund products offered by the bank to customers are deposits. Deposits are deposits that can be withdrawn only at a specifc time based on an agreement between the customer and the bank. Depositing money in the bank is one means of proftable investments . But on the other hand, in recognition of usury in the public interest to make the banks are having doubts on deposit products. This article tries to fnd out how Islamic legal review of the deposits .Keywords: deposits, bank, Islamic law